Life force and death force in - Sandra Sirangelo Maggio (Ilha do Desterro)
Frieda Lawrence first introduced her husband to the work of Sigmund Freud when the last draft of Sons and Lovers was being finished. That's why critics, even now, wonder about the extent of the influence Fredian theories might have had upon the novel. Anyway, the fact remains that Lawrence has his own views of the unconscious (which he states in essays such as 'Fantasia of the Unconscious' and 'Psychoanalysis of the Unconscious') 1 , and that he and Freud follow, ultimately, the same path. Sons and Lovers is where they meet, one with theoretic explanations, the other with the empirical demonstration.